She's Got a Ticket to Ride: Gender and Public Transit Passes - Colin Vance; Matthias Peistrup (Transportation, 2012)
The promotion of public transit is a central policy tool in the German government's efforts to mitigate pollution, congestion, and other automobile-caused externalities. Drawing on a household survey spanning 1997-2007 from Germany, this analysis investigates the decision to purchase a weekly or monthly transit pass against the backdrop of two questions: 1) Does gender play a role in determining the probability that an individual owns a pass? 2) If so, how is this role mitigated or exacerbated by other socioeconomic attributes of the individual and the household in which they reside? These questions are pursued through a combination of descriptive analyses and econometric methods, the latter of which relies on variants of the probit- and heteroskedastic probit model to control for the effects of unobserved heterogeneity that could otherwise induce biased estimates. The model uncovers several determinants of transit pass patronage over which policy makers have direct leverage, including fares, fuel prices, and the siting of transit stops. Moreover, while women are found to have a higher probability of owning a transit pass than men, the model identifies few variables whose impact differs according to gender, with the two exceptions being the number of children in the household and the distance to work. This absence of differential effects implies that policy measures to increase ridership are likely to have a roughly uniform impact among women and men.
Keywords: 330; public transit; household data; heteroskedastic probit